JUDUL GREBEG SURO: TRADISI RITUAL DAN MAKNANYA DALAM BUDAYA JAWA DI DAERAH KEDIRI - Hari Pratiwi, Aisyah (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
Tradition and culture shape the identity of Indonesia's ethnically diverse society, with Grebeg Suro in Kediri, East Java, a lasting local wisdom. Celebrated every 1 Suro in the Javanese calendar, this tradition is rooted in the acculturation of ancient Javanese spiritual values ​​and Islamic teachings dating back to the 15th century. This tradition serves as an expression of gratitude to God, respect for ancestors, and an effort to ward off disasters to maintain harmony in life. This research uses a qualitative descriptive approach through participatory observation of the ritual procession and in-depth interviews with traditional leaders, organizers, and local communities, to explore the cultural phenomenon in depth from a local perspective. The research results show that the implementation of Grebeg Suro involves a series of activities such as processions, meditation, grave pilgrimages, and traditional art performances (shadow puppets, jaranan, barongan), which are not only ceremonial but also rich in symbolic meaning. Spiritually, this tradition encourages introspection and self-purification; socially, it strengthens cooperation and solidarity. Amidst modernization, Grebeg Suro functions as a cultural resistance against the erosion of local values, strengthening national identity through the transmission of ethical values ​​across generations.